Spiritual tech and democracy: initial ethical reflections - Max Tretter (Frontiers in Political Science)
The relationship between religion and democracy is ambivalent, with religion either able to strengthen democracy or significantly threaten it. With the “digital turn” in religion and the growing prevalence of spiritual tech—such as digital religious platforms, apps specialized on spirituality, and religious chatbots powered by Artificial Intelligence—this relationship becomes even more intricate. In this Perspective, I will explore the fundamental relationship between religion and democracy and then outline the different ways in which spiritual tech can influence democratic processes. I will demonstrate that there are currently no legitimate national or international measures in place to limit the democracy-threatening potential of spiritual tech. To address this gap, I propose introducing a structured review process designed to actively promote spiritual tech that supports and strengthens democratic values.